Pengaruh Komitmen Organisasional, Kepuasan Kerja dan Budaya Organisasi terhadap Kinerja Karyawan pada Bento Kopi Yogyakarta - Rian Fajar Sidik; Jajuk Hermawati; Soni Kurniawan (Widya Manajemen, 2021)
The purpose of this study was to determine the analysis of the influence of organizational commitment, job satisfaction, and organizational culture on employee performance at Bento Kopi Yogyakarta. In this study, the target population is all employees of Bento Kopi Yogyakarta, both permanent and contractual. The sample of this study is part of the target population is 100 employees of Bento Kopi Yogyakarta, where the sample is determined by the Slovin formula. The data was collected using a questionnaire or questionnaire collection method. The data analysis technique used is the regression technique which is supported by the t test and classical assumptions, the data that has been obtained are processed using SPSS 21. The results of this study indicate that organizational commitment has a positive and significant effect on employee performance in accordance with the significance test carried out by the test- t and obtained tcount> ttable (61.695> 1.66055) sig. amounting to 0.000 / 0.0 so that Ho is rejected and Ha is accepted, job satisfaction has a positive and significant effect on employee performance in accordance with the significance test carried out by t-test and obtained tcount> ttable (38.241> 1.66055) sig. 0.00 / 0.00 so that Ho is rejected and Ha is accepted, organizational culture has a positive and significant effect on employee performance in accordance with the significance test carried out with the t-test and obtained tcount> ttable (35.798> 1.66055) sig. 0,000 so that Ho is rejected and Ha accepted.